2019
DOI: 10.1177/0269216319852007
|View full text |Cite
|
Sign up to set email alerts
|

Communication between healthcare professionals and relatives of patients approaching the end-of-life: A systematic review of qualitative evidence

Abstract: Background: Effective communication between healthcare professionals and relatives of patients approaching the end-of-life is vital to ensure patients have a ‘good death’. To improve communication, it is important to first identify how this is currently being accomplished. Aim: To review qualitative evidence concerning characteristics of communication about prognosis and end-of-life care between healthcare professionals and relatives of patients approaching the end-of-life. Design: Qualitative systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(155 citation statements)
references
References 68 publications
9
129
0
1
Order By: Relevance
“…This supports our findings that learners consider acknowledging uncertainty and providing information, checking what the patient understands, and asking what they want to know, as key to prognostic communication. Anderson et al (2019) found that 'highlighting deterioration' was an important element, which involves detailing past and current health problems to emphasise end of life was approaching [24]. The promise of ongoing, continuing care was underlined as essential [24], which is consistent with our findings.…”
Section: Acknowledging and Communicating Prognostic Uncertaintysupporting
confidence: 87%
See 2 more Smart Citations
“…This supports our findings that learners consider acknowledging uncertainty and providing information, checking what the patient understands, and asking what they want to know, as key to prognostic communication. Anderson et al (2019) found that 'highlighting deterioration' was an important element, which involves detailing past and current health problems to emphasise end of life was approaching [24]. The promise of ongoing, continuing care was underlined as essential [24], which is consistent with our findings.…”
Section: Acknowledging and Communicating Prognostic Uncertaintysupporting
confidence: 87%
“…Individualised or patient-centred care has been identified as an essential component of a safe and high-quality health system in Australia [23]. Patient-centred care, as highlighted in our study, includes the basic tenets of patients and/or family involvement in decision-making [24], of open communication between patients, families, and HCP [25], of sharing power and responsibility, and of accepting patients' life choices [22]. Patients' values, priorities, and goals are considered central to this care planning process, although patients do need to have an understanding of their illness to be able to participate fully in any discussions [26].…”
Section: Patient-centred Carementioning
confidence: 96%
See 1 more Smart Citation
“…4,[7][8][9][10] It requires the establishment of a dynamic caring relationship with the patient and family to reduce suffering, and also among nurses themselves and the multi-professional healthcare team. [11][12][13][14][15][16][17][18][19][20][21] Although nursing and palliative care share common roots, goals, and values, to advance palliative care nursing practice, it is essential to discern the unique contribution of nursing to the field of palliative care. The goal of palliative care is to prevent and relieve suffering, and to support the best possible quality of life for patients and their families, regardless of the stage of the disease or the need for other therapies.…”
Section: Introductionmentioning
confidence: 99%
“…As they are dying of the same life‐limiting illnesses as experienced by the general population, people with intellectual disabilities also require the same end‐of‐life care that the rest of the population are being provided with (Coppus, 2013; Tuffrey‐Wijne et al., 2016). Furthermore, it must be pointed out that during such an uncertain time, effective communication is essential between patients, family members and service providers in order to improve the quality of care provided at the end of life (Anderson, Bloch, Amstrong, Stone, & Low, 2019; Brinkman‐Stoppelenburg, Rietjens, & van der Heide, 2014). Also, such conversation helps people with intellectual disabilities understand their clinical situation, decide what kind of care they require, and how they wish to plan towards the end of their life (Ryan, Guerin, Dodd, & McEvoy, 2011; Wagemans et al., 2015).…”
Section: Introductionmentioning
confidence: 99%